Data integration issues in the reconstruction of the genome-scale metabolic model of Zymomonas mobillis - Pinto, José P. (2009)
Genome-scale model reconstruction represents a major tool in the field of Metabolic Engineering .This paper reports on a study about data integration issues in the process of genome- scale reconstruction of the metabolic model of the bacterium Zymomonas mobilis, a promising organism for bioethanol production. Data is retrieved from the Entrez Gene, KEGG, BioCyc and Brenda databases, and the several processes involved in data integration from these sources are described, as well as the data quality issues.